An evaluation of tofacitinib for the treatment of psoriatic arthritis. (2nd November 2019) - Abdulrahim, Hunar; Sharlala, Hisham; Adebajo, Adewale O.
ABSTRACT: Introduction : Psoriatic arthritis (PsA) is a chronic inflammatory condition that is associated with progressive joint destruction and reduced quality of life. Despite the common use of disease-modifying anti-rheumatic drugs (DMARDs) in PsA, their influence has been investigated in a number of studies with conflicting results. There is also concern about their safety and tolerability. Tofacitinib is an orally administered Janus kinase (JAK) inhibitor that has recently been approved for the treatment of PsA by various international regulatory authorities, including the FDA, EMA, and NICE. Areas covered : In this review, the mechanism of action and the pharmacokinetic properties of tofacitinib are discussed. The data from two large phase III clinical studies evaluating the use of tofacitinib in PsA is also discussed in addition to the findings from other relevant studies. Expert opinion : The clinical data demonstrate significant improvement in disease activity in PsA patients using tofacitinib. There is also an acceptable clinical safety profile for the drug. Tofacitinib has various advantages over several existing drug treatments for PsA including an oral route of administration, a short half-life and a fast onset of action. Consequently, we anticipate that tofacitinib will become an increasingly used targeted synthetic DMARD (tsDMARD) for active PsA over the coming years.